Association of single and multiple prefluoroalkyl substances exposure with preterm birth: Results from a Chinese birth cohort study. (November 2022) - Liao, Qian; Tang, Peng; Song, Yanye; Liu, Bihu; Huang, Huishen; Liang, Jun; Lin, Mengrui; Shao, Yantao; Liu, Shun; Pan, Dongxiang; Huang, Dongping; Qiu, Xiaoqiang
Abstract: Background: Perfluoroalkyl substances (PFASs) are persistent organic pollutants that may lead the adverse birth outcomes, including preterm birth (PTB). However, previous studies have reported inconsistent results on the association between PFASs and PTB, and lack of the epidemiological evidence regarding the effect of PFASs mixture on PTB. This study aimed to explore association of individual and multiple exposure to PFASs with PTB. Methods: The study subjects were consisted of 1341 pregnant women from Guangxi Zhuang Birth Cohort in Guangxi, China, from June 2015 to April 2019. Nine PFASs concentrations in the maternal serum were examined by ultrahigh liquid performance chromatography-tandem mass spectrometry, and the gestational weeks were obtained from medical records. We applied binary logistics regression model to explore correlation between individual PFAS and PTB and inspected the combined effect of PFASs mixture on PTB by applying Bayesian kernel machine regression (BKMR) and weighted quantile sum (WQS) regression models. Results: In adjusted logistics regression model, perfluorooctane sulfonate (PFOS), perfluoroheptanoic acid (PFHpA), perfluorobutanesulfonic acid (PFBS), ∑perfluorinated sulfonic acids (PFSA), and ∑PFASs were positively associated with the risk of PTB. In contrast, perfluoroundecanoic acid (PFUnA), perfluorohexane sulfonate (PFHxS), and perfluorooctanoic acid (PFOA) were negatively associated with the risk of PTB. These associations of n PFOS and PFHpA with PTB were found to be more pronounced in male infants. Restricted cubic splines (RCSs) showed an inverse U-shaped relationship between PFBS and PTB. Analysis from BKMR model showed a positive association between PFASs mixture and PTB, and no evidence of interactions among the nine PFASs were detected. Additionally, PFHpA, PFOS, and PFBS were identified as the main contributors for the effect of PFASs mixture on increasing the risk of PTB by BKMR and WQS models. Conclusion: Prenatal exposure to higher levels of PFASs mixture was associated with higher risk of PTB. Graphical abstract: Image 1 Highlights: Prenatal exposure to PFASs mixture was related to higher risk of PTB. PFHpA(33.6%), PFOS(31.8%), and PFBS(18.9%) were main contributors in association with higher risk of PTB. An inversely U-shaped relationship was observed between PFBS and PTB. PFOS and PFHpA with PTB were sex-specific.